Meaning of Corporate Advertising of PT. The Chevron “We Agree” On Television (Semiotic Analysis by Roland Barthes) - Ruwianti Dian Permatasari (COMMENTATE: Journal of Communication Management, 2022)
Advertising can be said to have become one of the media to convey various messages aimed at certain people because of its broad nature and covering various groups because of the ease of access to view it. PT. Chevron, one of the companies engaged in the oil and gas sector, is also aware of the effects of one of these mass media. Therefore, PT. Chevron also uses advertising media to display its corporate advertisement version of “We Agree” which in 2016 was broadcast through various television media. This study uses a qualitative method with a semiotic approach by Roland Barthes as a tool for analyzing various signs so as to form denotative, connotative and mythical meanings contained in the advertisement. This analysis also criticizes a dilemma faced by companies related to ecology. In Roland Barthes' semiotic perspective, the researcher found various meanings contained in the advertisement, namely Chevron gives a picture of progress in a society, namely if that civilization has various tall buildings that tower as a form of progress of the times, even though several other countries have proven that reforestation is also is one of the markers of the progress of a society. However, this does not change the fact that Chevron is a company that contributes to the economy and human empowerment which then makes Chevron one of the foreign companies in Indonesia that also pays attention to the development of the Indonesian State.